Dissipative Hyperbolic Geometric Flowon Modified Riemann Extensions - Nagaraja, H. G.; D., Harish (Communications in Mathematics and Applications, 2015)
We study the properties of modified Riemann extensions evolving under dissipative hyperbolic geometric flow with examples.